Aspek Gramatikal dan Leksikal pada Lirik Lagu Jangan Rubah Takdirku Karya Andmesh Kamelang - Goziyah, Goziyah; Uyun, Iin Inarotul; Fabiola, Shella (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research was to describe the grammatical and lexical aspects in the lyrics of the song Jangan Rubah Takdirku by Andmesh Kamelang. The research method uses microstructural methods. The collection technique uses documentation techniques by downloading the song Jangan Rubah Takdirku via Youtube. The main instrument in this research is the researcher who is assisted by a device. Data analysis techniques by means of data reduction, data tabulation, data display, interpretation, and conclusions. Test the validity of the data using membercheck and validation from literary experts. The results showed that the grammatical and lexical aspects in the lyrics of the song Jangan Rubah Takdirku, sung by Andmesh Kamelang, present a deep meaning about the life journey of a person who is full of hard work, loyalty, and hope of love for someone he loves. Grammatical aspects and lexical aspects build up each other so that the song Jangan Rubah Takdirku becomes a song that impresses the listeners. The grammatical aspect found in the song is referencing marked by the presence of the word dia and impingement by the presence of each word. Then, the lexical aspect that was found was repetition which was marked by the presence of the words I want, in each, and I did not, and synomini was marked by the presence of the words weak and shaky.